Evaluation of workshop on teaching skills for medical postgraduates (Ramachandra Annual Postgraduate Teaching Skills) - K Dilara; R Padmavathi; K Maheshkumar; S Anandan; P V Vijayaraghavan (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Postgraduate medical curriculum is usually devoted to developing competencies in the specialty concerned, patient care, and submitting dissertations. The need to impart teaching skills during postgraduation has gone unnoticed, hence Ramachandra Annual Postgraduate Teaching Skills (RAPTS), a teaching skills workshop, was conceptualized and implemented as postgraduate students serve as tutors/residents in the department to teach undergraduate medical students. This study is aimed to evaluate the effectiveness of the teaching skills workshop for postgraduates. MATERIALS AND METHODS: One hundred and seventy-eight postgraduate students of pre- and paraclinical department underwent the training in medical education principles and participated in the feedback. RAPTS Workshop was implemented as per the six-step approach. The learning was evaluated through a pre- and posttest scores. Student feedback was also obtained on the process overall objectives and contents of the workshop. Force-field analysis was performed. RESULTS: There was a significant learning by the postgraduates on various medical education principles as evidenced by significant improvement in the posttest scores (P < 0.05). Feedback regarding the general aspects of the workshop showed that 92% of the participants felt that the contents of the workshop suited their learning. Eighty-four percent of the participants opined that the presentations of the sessions were good and 91% felt that time management was good. Force-field analysis indicated that the factors favoring teaching skills workshop were higher. CONCLUSION: This study has highlighted the importance of including teaching methodology training in the postgraduate curriculum that helps in grooming the future teachers in the right direction, in the right time. Competencies related to teaching skills based on medical education principles can be included in the postgraduate curriculum.